Youth Comes But Once in a Lifetime for Adult-Born Neurons. Issue 9 (September 2018) - Sailor, Kurt A.; Lledo, Pierre-Marie
Abstract : Using new methods to functionally dissect circuits, two papers from 2015 found enhanced synaptic properties of the inputs and outputs of hippocampal adult-born neurons specifically during a critical period of their development. These studies provided a circuit-level view of unique roles for new neurons and how they cope with the ever-changing environment.